The Corona Virus Disease 2019 (COVID-19) - World Health Organization (Brazilian Journal of Implantology and Health Sciences, 2022)
This file is only intended to update and facilitate access to the “The Corona Virus Disease 2019 (COVID-19)” section of the World Health Organization. Follow the link to access the necessary information: https://www.who.int/emergencies/diseases/novel-coronavirus-2019